85.4k views
0 votes
Which quadratic equation is equivalent to (x2 – 1)2 – 11(x2 – 1) + 24 = 0?

2 Answers

2 votes

Answer:

option 1

Explanation:

User Omar Makled
by
4.3k points
4 votes

Answer:

u² – 11u + 24 = 0 where u = (x² – 1)

Explanation:

Given the equation;

(x² – 1)² – 11(x² – 1) + 24 = 0

We can let;

u = x² - 1

Substituting the value of u in the equation we get;

(u)² - 11 (u) + 24 = 0

u²- 11u + 24 = 0

Therefore;

The quadratic equation that is equivalent to the equation is;

u² – 11u + 24 = 0 where u = (x² – 1)

User Chokrijobs
by
4.8k points